Detection and characterization of free oxygen radicals induced protein adduct formation in differentiating macrophages - Manoharan, Renuka Ramalingam; Sedlářová, Michaela; Pospíšil, Pavel; Prasad, Ankush (Biochimica et biophysica acta. G, General subjects, 2023)
Reactive oxygen species play a key role in cellular homeostasis and redox signaling at physiological levels, where excessive production affects the function and integrity of macromolecules, specifically proteins. Therefore, it is important to define radical-mediated proteotoxic stress in macrophages and identify target protein to prevent tissue dysfunction. A well employed, THP-1 cell line was utilized as in vitro model to study immune response and herein we employ immuno-spin trapping technique to investigate radical-mediated protein oxidation in macrophages. Hydroxyl radical formation along macrophage differentiation was confirmed by electron paramagnetic resonance along with confocal laser scanning microscopy using hydroxyphenyl fluorescein. Lipid peroxidation product, malondialdehyde, generated under experimental conditions as detected using swallow-tailed perylene derivative fluorescence observed by confocal laser scanning microscopy and high-performance liquid chromatography, respectively. The results obtained from this study warrant further corroboration and study of specific proteins involved in the macrophage activation and their role in inflammations.
Keywords: reaktivní formy kyslíku; Electron Spin Resonance Spectroscopy; Spin Trapping; volné radikály; elektronová paramagnetická rezonance; proteiny; Proteins; Macrophages; spin trapping; Reactive Oxygen Species; makrofágy; Free Radicals